(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
Nickel, vanadium and magnesium ions were extracted from the heavy fuel residues used in electrical power stations and heating furnaces of production units. This extraction was done by organic ester-phosphorous ligands and amputated amines. To separate these ions from the residue, a small laboratory device was designed for separation in two stages: first, base dissolution to dissolve and deposite the vanadium oxide with an ammonized, amputated compound. Second, Sour dissolution of both oxide nickel and oxide vanadium and the extraction of their ions through selective phosphoric compounds, organic soil such as: 1 - (C16H14PSNO3) O-(quinolin-8-yl) (o-tolyl) thio-hydrogen phosphate. .(O-(quinolin-8-yl) (o-tolyl) hydrogen phosphate (C16H14PNO4)- 2 O-phenyl O-(8-quinolin) thio hydrogen phosphate. 3 - (C15H12PSNO3)